2022
DOI: 10.3389/fgene.2022.949252
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanism of histone lactylation in health and diseases

Abstract: Whether under anaerobic or aerobic conditions, glycolysis results in production of lactate. Increasing evidence suggests that lactate serves as a multifunctional signaling molecule that develops non-metabolic activities in addition to serving as a key metabolite to link glycolysis and oxidative phosphorylation. Histone posttranslational modification patterns (HPTMs) are essential epigenetic processes controlling a variety of biological activities. Proteomics based on mass spectrometry (MS) has been used to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Numerous histone modifications, including acetylation, methylation, and crotonylation, have been documented before the 2019 discovery of histone lactylation. Recent findings by Zhao et al state that lactate contributed to epigenetic regulation of genes by lactylating histone lysine residues and that lactate was found to be a precursor to histone lysine lactylation (Kla), which stimulated gene transcription from chromatin [ 24 , 25 ]. Histone lactylation is first reported to promote homeostasis of macrophages during infection, and more and more studies have focused its role in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous histone modifications, including acetylation, methylation, and crotonylation, have been documented before the 2019 discovery of histone lactylation. Recent findings by Zhao et al state that lactate contributed to epigenetic regulation of genes by lactylating histone lysine residues and that lactate was found to be a precursor to histone lysine lactylation (Kla), which stimulated gene transcription from chromatin [ 24 , 25 ]. Histone lactylation is first reported to promote homeostasis of macrophages during infection, and more and more studies have focused its role in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3,172 In recent years, the study of epigenetic modifications has gained significant attention, and histone lactylation has been discovered to play a crucial role in immune regulation, inflammation, cancer, and other diseases. [173][174][175][176] The p300 of HAT family mediates the lactylation modification of H3 and H4, while the deacetylases HDAC1-3 and SIRT1-3 have the de-L-lactylase enzyme activity. 171 These results indicate that histone lactate is also a reversible process.…”
Section: Histone Lactylationmentioning
confidence: 99%
“…found that global H3K18 lactylation distribution marked the active promoter regions of some highly expressed genes, which was positively correlated with gene expression 3,172 . In recent years, the study of epigenetic modifications has gained significant attention, and histone lactylation has been discovered to play a crucial role in immune regulation, inflammation, cancer, and other diseases 173–176 …”
Section: Ptms Of Histonesmentioning
confidence: 99%
“…93,94 It may act as a signaling molecule and regulate gene expression by acting at the epigenetic level as a precursor of lactylation of histones. 95,96 Glycogen, a form of glucose storage, was also identified as a discriminant metabolite. In Drosophila, it is synthesized and stored mainly in muscles and the fat body.…”
Section: Metabolism Is Modified In Glioma-bearing Fliesmentioning
confidence: 99%